2016
DOI: 10.3390/su8060528
|View full text |Cite
|
Sign up to set email alerts
|

Policy Mixes to Achieve Absolute Decoupling: An Ex Ante Assessment

Abstract: Abstract:One approach to reducing the environmental costs of economic activity is to design and implement policies that aim at decoupling economic activity from its environmental impacts. Such a decoupling requires an economy-wide approach to policy-making, through broad mixes of policy instruments that create the right framework conditions for decoupling, and which provide coherent and consistent signals to resource-using sectors of the economy. This article summarizes the ex ante qualitative environmental as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…By reviewing the resulting articles, a wide range of policy instruments and policy approaches were identified. By juxtaposing the list of CBM barriers with identified policy interventions from the literature (Domenech & Bahn‐Walkowiak, 2019; Ekvall et al, 2016; Hartley et al, 2020; Hirschnitz‐Garbers et al, 2016; McDowall et al, 2017; Watkins et al, 2016; Wilts et al, 2015), 15 policies in total were found to be direct responses to the barriers in Table 3. A brief description of the identified policy interventions is presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By reviewing the resulting articles, a wide range of policy instruments and policy approaches were identified. By juxtaposing the list of CBM barriers with identified policy interventions from the literature (Domenech & Bahn‐Walkowiak, 2019; Ekvall et al, 2016; Hartley et al, 2020; Hirschnitz‐Garbers et al, 2016; McDowall et al, 2017; Watkins et al, 2016; Wilts et al, 2015), 15 policies in total were found to be direct responses to the barriers in Table 3. A brief description of the identified policy interventions is presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the extensive literature on CBM barriers, the literature focusing on the enabling policy interventions for CE is rather limited and mainly consists of macro top‐down policy frameworks for resource efficiency (Domenech & Bahn‐Walkowiak, 2019; Ekvall, Hirschnitz‐Garbers, Eboli, & Śniegocki, 2016; Hartley, van Santen, & Kirchherr, 2020; Hirschnitz‐Garbers et al, 2016; McDowall et al, 2017; Watkins, ten Brink, Schweitzer, Rogissart, & Nesbit, 2016; Wilts et al, 2015). Recently, emerging literature is taking a case study approach on targeted policy interventions regarding specific CBM barriers (Milios, Beqiri, Whalen, & Jelonek, 2019; Nußholz, Rasmussen, & Milios, 2019; Öhgren, Milios, Dalhammar, & Lindahl, 2019; Wasserbaur & Milios, 2019; Whalen, Milios, & Nussholz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Todėl svarbu sistemiškai išanalizuoti TI sistemos tikslų raidą, jų sąsajas su tvarumo dimensijomis bei sukurti TI sistemos poveikio vertinimo modelį. Nors didėjanti paklausa dėl politikos poveikio vertinimo socialiniu, ekonominiu ir aplinkosaugos aspektu suponavo kombinuoto taikymo skirtingų modelių ir įrankių sukūrimą (Britz 2008), literatūroje aptikta tik modelių, vertinančių integruotą perspektyvinį (ex-ante) BŽŪP poveikį (Britz 2008;Van Ittersum et al 2008;Ewert et al 2009;Piorr et al 2009;Janssen et al 2010;Helming et al 2011;Watkins et al 2016), neatsižvelgiant į atskiros priemonės poveikio vertinimą. Trūksta metodologinių principų, kurie leistų konstruoti vertinimo instrumentą, skirtą matuoti BŽŪP TI sistemos pažangą, didinant žemės ūkio tvarumą, atsižvelgiant į ekonominę, socialinę ir aplinkosauginę dimensijas.…”
Section: įVadas Problemos Formulavimasunclassified
“…Lygiagrečiai su integruoto tvarumo vertinimu didėjo paklausa dėl politikos poveikio vertinimo socialiniu, ekonominiu ir aplinkosaugos aspektais, ir tai nulėmė kombinuoto taikymo skirtingų modelių ir įrankių sukūrimą (Britz 2008). Literatūroje gausu modelių, kuriais atliekamas perspektyvinis (ex-ante) BŽŪP poveikio vertinimas (Britz 2008;Van Ittersum et al 2008;Ewert et al 2009;Janssen et al 2010;Piorr et al 2009;Helming et al 2011;Watkins et al 2016), tačiau modeliuose trūksta kiekybiškai įvertinto atskiros BŽŪP priemonės (pvz., TI sistemos) poveikio žemės ūkio tvarumui tiek einamuoju laiku, tiek praeityje (ex-post vertinimas). Vieni populiariausių perspektyvinių BŽŪP vertinimo modelių -CAPRI, SEAMCAP, SEAMLESS-IF, FSSIM.…”
Section: Rodikliai (116)unclassified
“…Recently, there has been growing interest in this field. A number of policy instruments and policy mixes for a more sustainable waste management have been suggested (e.g., [3][4][5]). …”
Section: Introductionmentioning
confidence: 99%